Factores de riesgo para adquirir la infección por el Virus del Papiloma Humano (VPH) y otras infecciones de transmisión sexual en mujeres estudiantes universitarias vacunadas y no vacunadas contra el VPH (2016)
ABSTRACT: Human Papillomavirus (HPV) infection is one of the most common Sexually Transmitted Infections (STIs) worldwide. Early initiation of sexual intercourse and a high number of sexual partners are the major risk factors for acquiring this and other STIs. Currently, vaccination against HPV is a major primary prevention strategy against this virus. The objective of this research was to describe the risk factors associated with HPV infection and other STIs in female university students, vaccinated and nonvaccinated against HPV infection. Methods: this cross-sectional descriptive study included a survey applied to female university students older than 18 years of age who had received or not the vaccine against HPV. The survey contained 50 questions about socio-demographic factors, risk factors for acquiring STIs and vaccination status against HPV. Sampling was done for convenience. The variables related to sexual behavior and risk factors for acquiring HPV infection and other STIs were categorized by assigning measurement values. The SPSS program was used to analyze the data. Results: Twenty-three percent (23.8%) of students reported that they had received the HPV vaccine. The majority of the unvaccinated female students had more than three sexual partners (P = 0.001), did not use condoms (P = 0.015) and used hormonal contraceptives (P = 0,018). Additionally, the majority of students vaccinated were under 20 years of age (P = < 0.001). Conclusions: the majority of unvaccinated students often are at a higher risk of acquiring HPV infection and other STIs.